A Bovine Enteric Mycobacterium Infection Model to Analyze Parenteral Vaccine-Induced Mucosal Immunity and Accelerate Vaccine Discovery - Facciuolo, Antonio; Lee, Amy H.; Trimble, Michael J.; Rawlyk, Neil; Townsend, Hugh G. G.; Bains, Manjeet; Arsic, Natasa; Mutharia, Lucy M.; Potter, Andrew; Gerdts, Volker; Napper, Scott; Hancock, Robert E. W.; et al. (Frontiers in Immunology, 2020)
Mycobacterial diseases of cattle are responsible for considerable production losses worldwide. In addition to their importance in animals, these infections offer a nuanced approach to understanding persistent mycobacterial infection in native host species. Mycobacteriumavium ssp. paratuberculosis (MAP) is an enteric pathogen that establishes a persistent, asymptomatic infection in the small intestine. Difficulty in reproducing infection in surrogate animal models and limited understanding of mucosal immune responses that control enteric infection in the natural host have been major barriers to MAP vaccine development. We previously developed a reproducible challenge model to establish a consistent MAP infection using surgically isolated intestinal segments prepared in neonatal calves. In the current study, we evaluated whether intestinal segments could be used to screen parenteral vaccines that alter mucosal immune responses to MAP infection. Using Silirum® – a commercial MAP bacterin – we demonstrate that intestinal segments provide a platform for assessing vaccine efficacy within a relatively rapid period of 28 days post-infection. Significant differences between vaccinates and non-vaccinates could be detected using quantitative metrics including bacterial burden in intestinal tissue, MAP shedding into the intestinal lumen, and vaccine-induced mucosal immune responses. Comparing vaccine-induced responses in mucosal leukocytes isolated from the site of enteric infection versus blood leukocytes revealed substantial inconsistences between these immune compartments. Moreover, parenteral vaccination with Silirum did not induce equal levels of protection throughout the small intestine. Significant control of MAP infection was observed in the continuous but not the discrete Peyer’s patches. Analysis of these regional mucosal immune responses revealed novel correlates of immune protection associated with reduced infection that included an increased frequency of CD335+ innate lymphoid cells, and increased expression of IL21 and IL27. Thus, intestinal segments provide a novel model to accelerate vaccine screening and discovery by testing vaccines directly in the natural host and provides a unique opportunity to interrogate mucosal immune responses to mycobacterial infections.